1995
DOI: 10.1128/jcm.33.8.2141-2144.1995
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genotyping of methicillin-resistant Staphylococcus aureus via fluorophore-enhanced repetitive-sequence PCR

Abstract: Methicillin resistance in Staphylococcus aureus is a frequent cause of nosocomial and community-acquired infections. Accurate, rapid epidemiologic typing is crucial to the identification of the source and spread of infectious disease and could provide detailed information on the generation of methicillin-resistant S. aureus (MRSA) strains. The high degree of genetic relatedness of MRSA strains has precluded the use of more conventional methods of genetic fingerprinting. A rapid DNA fingerprinting method that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(57 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…Antimicrobial resistances were determined by the automated instrument VITEK2 (bioMerieux, Marcy L'Etoile, France). The presence of resistance genes was investigated by PCR multiplex analysis adapted from methods previously described by Dutka-Malen et al [10] for van genes, or Del Vecchio et al [11] for mecA genes. Strains were grown on Mueller Hinton agar (BD, 225250) or in Mueller Hinton broth (MHB) (BD, 275730), complemented with 5% lysed sheep blood for the streptococci.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Antimicrobial resistances were determined by the automated instrument VITEK2 (bioMerieux, Marcy L'Etoile, France). The presence of resistance genes was investigated by PCR multiplex analysis adapted from methods previously described by Dutka-Malen et al [10] for van genes, or Del Vecchio et al [11] for mecA genes. Strains were grown on Mueller Hinton agar (BD, 225250) or in Mueller Hinton broth (MHB) (BD, 275730), complemented with 5% lysed sheep blood for the streptococci.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…It has been shown that this method is reproducible and accurate. Vecchio et al (1995) showed that their PCR products were highly reproducible and stable when trying to distinguish 170 stains of Mycoplasma pneumoniae using RW3A of RepMP3 as primer. Van der Zee et al (1999) showed that REP-PCR results were similar to pulse field gel electrophoresis (PFGE) analysis.…”
Section: Feces-5mentioning
confidence: 99%
“…Methicillin resistance was determined by oxacillin disk diffusion test and by oxacillin E test [24,28]. Isolates were confirmed to be methicillin resistant by polymerase chain reaction (PCR) for the mecA gene [29]. Phage typing was performed at the National Institute of Public Health and the Environment.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%